JS-K induces ferroptosis in renal carcinoma cells by regulating the c-Myc-GSTP1 Axis - Yuwan Zhao; LuGang Zhu; Xinghua Lin; Bin Li; Bailiang Miu; Jingping Qiu; Sheng Gao; Jianjun Liu (Scientific Reports)
Abstract JS-K is a precursor drug of nitric oxide (NO) and inhibits tumor growth through various mechanisms. Ferroptosis, a form of cell death closely related to lipid peroxidation, is increasingly being recognized for its role in cancer biology. However, the relevance of ferroptosis in the anti-tumor effects of JS-K is yet to be defined. The cytotoxic effects of erastin and JS-K were evaluated in various renal cell carcinoma (RCC) cell lines and normal human renal epithelial cells. Cell viability and the intracellular levels of ferrous ions, glutathione (GSH), lipid peroxides, and malondialdehyde (MDA) were measured using standard in vitro assays. The expression levels of specific proteins were analyzed by western blotting. Subcutaneous xenografts of RCC were established in a nude mouse model, and the anti-tumor effects of JS-K were assessed by histological and immunohistochemical methods. Erastin selectively inhibited the growth of RCC cells without affecting normal renal cells. In addition, JS-K induced ferroptosis in RCC cells by reducing cellular GSH levels, increasing lipid peroxidation, and elevating ferrous ion levels, and the effects of JS-K were neutralized by N-acetylcysteine (NAC). At the molecular level, JS-K downregulated GSTP1 by blocking the transcription factor c-Myc. Finally, JS-K inhibited tumor growth in a mouse model by inducing ferroptosis. JS-K induces ferroptosis in RCC cells by depleting glutathione through the inhibition of the c-Myc-GSTP1 axis.